Efficacy and safety of immune checkpoint inhibitors in young adults with metastatic melanoma. (March 2023) - Wong, Selina K.; Blum, Steven M.; Sun, Xiaopeng; Da Silva, Inês P.; Zubiri, Leyre; Ye, Fei; Bai, Kun; Zhang, Kevin; Ugurel, Selma; Zimmer, Lisa; Livingstone, Elisabeth; Schadendorf, Dirk; et al.
Abstract: Background: The integration of immune checkpoint inhibitors (ICI) for the treatment of melanoma has resulted in remarkable and durable responses. Given the potential role of immunosenescence, age may contribute to differential ICI efficacy and toxicity. While older patients have been studied in detail, outcomes from ICI in young patients (≤40 years) are not well characterised. Methods: We performed a multi-institutional, retrospective study of patients with advanced melanoma treated with anti-PD-1 monotherapy or ICI combination (ipilimumab and anti-PD-1). Response rates, survival, and toxicities were examined based on age comparing those under 40 years of age with older patients (age 41–70 and ≥ 71 years). Results: A total of 676 patients were included: 190 patients (28%) aged ≤40 years, 313 (46%) between ages 41–70, and 173 patients (26%) aged ≥71. Patients ≤40 years had higher response rates (53% vs 38%, p = 0.035) and improved progression-free survival (median 13.7 vs 4.0 months, p = 0.032) with combination ICI compared to monotherapy. Progression-free survival was similar among groups while overall survival was inferior in patients >70 years, who had low response rates to combination therapy (28%). ICIs had a similar incidence of severe toxicities, though hepatotoxicity was particularly common in younger patients vs. patients >40 with monotherapy (9% vs. 2%, p = 0.007) or combination ICI (37% vs. 10%, p < 0.001). Conclusions: ICIs had comparable efficacy between younger and older patients, although outcomes were superior with combination ICI compared to monotherapy in patients aged ≤40 years. Toxicity incidence was similar across age groups, though organs affected were substantially different. Highlights: Patients above and below 40 had similar outcomes to immune checkpoint inhibitors. Combination therapy produced particularly good outcomes in young patients. Hepatotoxicity was frequent in young patients with monotherapy and combo therapy. Young patients had similar mutation burdens but low T-cell activation signatures.